2002
DOI: 10.1164/rccm.2105079
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Interleukin-9 Antibody Treatment Inhibits Airway Inflammation and Hyperreactivity in Mouse Asthma Model

Abstract: Numerous in vitro and in vivo studies in both animals and patients with asthma have shown that interleukin (IL)-9 is an important inflammatory mediator in asthma. To examine the effects of IL-9 antagonism on airway inflammation, ovalbumin-sensitized BALB/c mice were intravenously given anti-IL-9 antibody or an isotype-matched control antibody 30 minutes before challenge with aerosolized ovalbumin. Airway response to methacholine was measured, and samples of bronchoalveolar lavage fluid (BALF) were obtained 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(123 citation statements)
references
References 52 publications
9
110
1
3
Order By: Relevance
“…In line with the present data, IL-9-deficient mice developed normal allergen-induced IgE levels (27,30) and lung inflammation upon pulmonary challenge (30). By contrast, other reports showed that anti-IL-9 Abs decreased IgE level and airway hyper-responsiveness in B6D2F 1 mice challenged with OVA (28) or airway inflammation and hyper-reactivity in BALB/c mice challenged with OVA (29).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with the present data, IL-9-deficient mice developed normal allergen-induced IgE levels (27,30) and lung inflammation upon pulmonary challenge (30). By contrast, other reports showed that anti-IL-9 Abs decreased IgE level and airway hyper-responsiveness in B6D2F 1 mice challenged with OVA (28) or airway inflammation and hyper-reactivity in BALB/c mice challenged with OVA (29).…”
Section: Discussionsupporting
confidence: 90%
“…Neutralizing IL-9 with an mAb decreased the IgE response, pulmonary eosinophilia, goblet cell hyperplasia, airway epithelial hyperplasia, and airway hyper-responsiveness in DBA/ 2 ϫ C57BL/6 F 1 mice (28). In another study, anti-IL-9 Ab administration to previously sensitized mice was able to prevent airway hyper-reactivity and lung eosinophilia upon aerosolized antigenic challenge (29). By contrast, in a similar OVA-induced asthma model, IL-9-deficient mice showed no decrease in allergic pulmonary airway hyperactivity, eosinophilia, goblet cell hyperplasia, or specific IgE (30).…”
Section: Il-9 Promotes But Is Not Necessary For Systemic Anaphylaxismentioning
confidence: 95%
“…Moreover, IL-9 deficiency in mice does not affect IL-4, or IL-13 T cell production (45,46). However, a recent study in a mouse model of asthma showed that anti-IL-9-neutralizing Ab reduced IL-4 and IL-13 levels in bronchoalveolar lavage of OVA-sensitized and -challenged mice (47). This inhibitory effect of neutralizing anti-IL-9 on Th2 cytokines (IL-4 and IL-13) may be explained by reduced recruitment of T cells to the lung, rather than inhibitory activity on T cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years various immunomodulators, including anti-IgE (11); anti-cytokine Abs (12,13); probiotics (14); CpG (15); synthetic YpG, CpR, and YpR immunostimulatory motifs (16); and mycobacterial Ags (17), which can up-regulate a type 1 T cell response, have shown therapeutic activity for allergen-induced asthma in both experimental animal models (2, 18) and a few clinical studies (19,20). However, many of these immunomodulators elicit serious side effects.…”
Section: Flt-3 Ligand Reverses Late Allergic Response and Airwaymentioning
confidence: 99%